Multifaceted Development and Application of Biopolymers for Biology, Biomedicine and Nanotechnology - Dutta, P.K.; Dutta, Joydeep; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
P. K. Dutta, Rohit Srivastava, Joydeep Dutta Functionalized Nanoparticles and Chitosan-Based Functional Nanomaterials Pallavi Pushp, Rajdeep Kaur, Hoon Taek Lee, Mukesh Kumar Gupta Nanoparticles for Gene Delivery into Stem Cells and Embryos Joydeep Dutta Engineering of Polysaccharides via Nanotechnology Arundhati Bhowmick, Subhash Banerjee, Ratnesh Kumar, Patit Paban Kundu Hydroxyapatite-Packed Chitosan-PMMA Nanocomposite: A Promising Material for Construction of Synthetic Bone Sanjeev K. Pandey, Chandana Haldar, Dinesh K. Patel, Pralay Maiti Biodegradable Polymers for Potential Delivery Systems for Therapeutics S. Maya, M. Sabitha, Shantikumar V. Nair, R. Jayakumar Phytomedicine-Loaded Polymeric Nanomedicines: Potential Cancer Therapeutics Dhanya Narayanan, J. Gopikrishna, Shantikumar V. Nair, Deepthy Menon Proteins and Carbohydrates as Polymeric Nanodrug Delivery Systems: Formulation, Properties, and Toxicological Evaluation Anil Kumar Anal, Alisha Tuladhar Biopolymeric Micro- and Nanoparticles: Preparation, Characterization and Industrial Applications Naresh Kottari, Yoann M. Chabre, Rishi Sharma, René Roy Applications of Glyconanoparticles as Sweet Glycobiological Therapeutics and Diagnostics
Functionalized Nanoparticles and Chitosan-Based Functional Nanomaterials -- Nanoparticles for Gene Delivery into Stem Cells and Embryos -- Engineering of Polysaccharides via Nanotechnology -- Hydroxyapatite-Packed Chitosan-PMMA Nanocomposite: A Promising Material for Construction of Synthetic Bone -- Biodegradable Polymers for Potential Delivery Systems for Therapeutics -- Phytomedicine-Loaded Polymeric Nanomedicines: Potential Cancer Therapeutics -- Proteins and Carbohydrates as Polymeric Nanodrug Delivery Systems: Formulation, Properties, and Toxicological Evaluation -- Biopolymeric Micro and Nanoparticles: Preparation, Characterization and Industrial Applications -- Applications of Glyconanoparticles as Sweet Glycobiological Therapeutics and Diagnostics.
Keywords: Chemistry; Microbiology; Microreactors; Polymers; Engineering; Nanotechnology; Chemistry; Polymer Sciences; Microengineering; Medical Microbiology; Nanotechnology; Nanotechnology and Microengineering